Anthologie Kulturpolitik: Einführende Beiträge zu Geschichte, Funktionen und Diskursen der Kulturpolitikforschung - Tröndle, Martin; Steigerwald, Claudia (transcript, 2019)
Classic and topical texts from Germany, Great Britain and the U.S. about the topic of "cultural policy«. A reader that defines the field of discourse and provides a look at the history of ideas about cultural policies.